Social Nervous Exercise Intervention and Its Association with Fasting Blood Glucose on Diabetes Mellitus Gestational - Afifah, Effatul; Nurdiati, Detty Siti; Hadi, Hamam; Sofro, Zaenal Muttaqien; Sadewa, Ahmad Hamim (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Gestational diabetes mellitus (GDM) has been identified as a major complication of pregnancies and has remained a major cause of perinatal morbidity and mortality, in both mother and child. Exercise can be used as a strategy to reduce hyperglycemia experienced during GDM. Regular exercise is important for a healthy pregnancy and can lower the risk of developing GDM. For women with GDM. Exercise is safe and can affect the pregnancy outcomes beneficially. The role of exercise about increases skeletal muscle glucose uptake and minimizing hyperglycemia. Social nervous (SaSo) exercise is a moderate-intensity exercise intervention that plays a role in controlling blood glucose through autonomic nervous stimulation so that it has an effect on glucose homeostasis. Social nervous exercise can stimulate the parasympathetic or myelinated vagus nerves. The social nerve or the social nervous system is the vagus nerve nc-X which is supported by cranial nerves, namely, nerves V, VII, IX, and XI centered in the nucleus ambiguous. AIM: The aim of the study is to determine the impact of a social nervous (SaSo) exercise training program consisting of warm-up, core (prayer movements), and cooling exercises on glucose homeostasis parameters in pregnant women diagnosed with GDM. METHODS: Thirty-seven pregnant women diagnosed with GDM at 24–28 weeks of gestation were allocated into two groups, thats the experimental group (n=19) with the SaSo program being regularly monitored and the control group (n=18) receiving only standard antenatal care for GDM. The Saso program started from the time diabetes was diagnosed until 6 weeks of intervention. Interventions were performed twice per week and sessions lasted 40–45 min. RESULTS: The baseline results for the experimental and control groups were homogeneous, without differences in the baseline variables (p > 0.05). Social nervous exercise the experimental group significantly reduced fasting blood glucose levels (p < 0.001) compared to the control group. CONCLUSIONS: A social nervous exercise program has a beneficial effect on fasting blood glucose levels in late pregnancy.